The Effectiveness of a Play-Based Program in Developing Some Linguistic Skills Among Kindergarten Children in Zakho Independent Administration, Kurdistan Region of Iraq - Ali Suleiman, Hikmat Mohammad; Mohammad, Nasraddin Ebrahim (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study investigates the effectiveness of a play-based program in developing linguistic skills, specifically listening and speaking, among kindergarten children aged 5-6 years. Using a one-group experimental design, the research was conducted in Zakho, Kurdistan Region of Iraq, with a sample of 35 kindergarten children (18 males, 17 females). The program consisted of 14 sessions over seven weeks, incorporating various educational games and storytelling activities designed to enhance auditory discrimination, visual discrimination, pronunciation accuracy, and verbal expression. Pre and post-tests measured the development of linguistic skills using standardized assessment tools. Statistical analysis using paired sample t-tests revealed significant improvements in both listening skills (t=14.36, p<0.05) and speaking skills (t=6.34, p<0.05) following the intervention, with large effect sizes of 2.42 and 1.07 respectively. Additionally, gender-based analysis demonstrated statistically significant differences favouring females in skills acquisition. The findings confirm the effectiveness of play-based learning in enhancing linguistic competencies among kindergarten children and provide valuable insights for educators and curriculum developers in early childhood education, highlighting the importance of interactive, play-based approaches in developing fundamental language skills in early childhood.